Tari Kleting Sumandhing In Sanggar Andhe Andhe Lumut - Yasmin, Alysa; Aminudin, Aminudin; Suharji, Suharji; Wibowo, Anggono Kusumo (Institut Seni Indoensia Surakarta, 2025)
This research aims to describe the form and creative process of creating the Tari Kleting Sumandhing. The method used in this study is descriptive qualitative research through observational data collection, interviews, and literature studies. The result of this research is the form of the Sumandhing Kleting Dance which consists of movement, dancers, makeup, and clothing, floor patterns, accompaniment music and staging venues. So that the dance form finds beautiful choreography and can be felt by the five senses. Meanwhile, the creative process is the process of thinking in creating, expressing, and creating the visuals of the Tari Kleting Sumandhing. This creative process involves deep exploration to translate values into symbolic forms of movement. The visualization of this symbol is expressed by thinking creatively as a process of imagining combining feelings and movements to find the expression of the character or figure of Kleting Kuning.